Tree–Crop Ecological and Physiological Interactions Within Climate Change Contexts: A Mini-Review - Gonçalves, Berta; Morais, Maria Cristina; Pereira, Sandra; Mosquera-Losada, Maria Rosa; Santos, Mário (Frontiers in Ecology and Evolution, 2021)
The effects of climate change are increasingly noticed worldwide, and crops are likely to be impacted in direct and indirect ways. Thus, it is urgent to adopt pliable strategies to reduce and/or mitigate possible adverse effects to meet the growing demand for sustainable and resilient food production. Monoculture cropping is globally the most common production system. However, adaptation to ongoing climate change, namely to more extreme environmental conditions, has renewed the interest in other practices such as agroforestry, agroecology, and permaculture. This paper provides an overview of ecological and physiological interactions between trees and crops in Mediterranean agroforestry systems, and compare them with those from monocultures. The advantages and disadvantages of both systems are explored. The added-value of modeling in understanding the complexity of interactions within agroforestry systems, supporting decision-making under current and future weather conditions is also pinpointed. Several interactions between trees and crops might occur in agroforestry systems, leading to mutual positive and/or negative effects on growth, physiology, and yield. In this sense, selecting the most suitable combination of tree/crop species in mixtures may be best be indicated by complementary in traits, which are crucial to maximize trade-offs, improving productivity, ecosystem services and environmental sustainability.